Implementation of the Problem Based Learning (PBL) Model to Improve Critical Thinking Skills of Grade V Students in the PKN Subject at SDN 62 Kota Bima - Muammar Muammar; Yayuk Kusumawati; Ikhsan Maulana (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to analyze the implementation of the Problem-Based Learning (PBL) model in improving critical thinking skills of fifth-grade students in Civics Education (PKN) at SDN 62, Bima City. The background of this study is based on the results of initial observations that indicate that the learning process in fifth grade is still dominated by simple lecture and question-and-answer methods, so that students tend to be passive and less involved in the process of in-depth thinking. This study uses a qualitative approach with descriptive methods. Data collection was carried out through observation, in-depth interviews, and documentation. Research informants included the principal, class teachers, and students. Data analysis was carried out interactively through the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the PBL model in Civics learning is able to encourage students to actively identify problems, analyze information, and formulate solutions systematically. Through contextual problem-based learning, students are trained to think analytically, argumentatively, and systematically. Thus, the PBL model can be an effective strategy in improving the critical thinking skills of elementary school students.